Pembelajaran Seni Budaya di SMP Negeri 3 Lengayang Kabupaten Pesisir Selatan - Feby Yola Pradana; Marzam Marzam (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
The research aims to describe the teaching and learning process of Cultural Arts at SMP N 3 Lengayang, Pesisir Selatan Regency. The method was qualitative research to describe the quality of the teaching and learning process descriptively. The subjects of this study were students of SMP Negeri 3 Lengayan, where one of the focuses was on class VII.I. Data analysis techniques utilizing observation, interviews and literature study. Once obtained, the data is then described in the research results. The results of this study were obtained during the observation and teaching and learning process employing direct interpretation with students. In the Lesson Plan, the material to be studied is about the art of Similar and Mixed Ensemble music. During the teaching and learning process, the teacher asked the students to have group discussions about the learning material. Students conduct discussions well about the learning material. However, students cannot fully understand because of the lack of learning media at the school.